Adverse Drug Reactions Relevant to Drug Resistance and Ineffectiveness Associated with Meropenem, Linezolid, and Colistin: An Analysis Based on Spontaneous Reports from the European Pharmacovigilance Database - Bogdan Ioan Vintila; Anca Maria Arseniu; Anca Butuca; Mihai Sava; Victoria Bîrluțiu; Luca Liviu Rus; Dan Damian Axente; Claudiu Morgovan; Felicia Gabriela Gligor (MDPI AG, 2023)
Antimicrobial resistance is considered one of the major threats to public health and is an important factor that influences the patient's outcome in the intensive care unit. Pharmacovigilance can help raise awareness of potential drug resistance (DR) or ineffectiveness (DI) through adverse drug reaction reports that are submitted to different spontaneous reporting systems. Based on spontaneous Individual Case Safety Reports from EudraVigilance, we conducted a descriptive analysis of adverse drug reactions associated with meropenem, colistin, and linezolid, with a focus on DR and DI. Of the total adverse drug reactions (ADRs) reported for each analyzed antibiotic by 31 December 2022, between 2.38-8.42% and 4.15-10.14% of the reports were related to DR and DI, respectively. A disproportionality analysis was conducted to evaluate the frequency of reporting adverse drug reactions relevant to the DR and DI of the analyzed antibiotics compared to other antimicrobials. Based on the analysis of the collected data, this study underlines the importance of post-marketing drug safety monitoring in raising a warning signal regarding antimicrobial resistance, thereby potentially contributing to the reduction in antibiotic treatment failure in an intensive care setting.